Post-COVID-19 condition: an online survey by questionnaire on 250 participants recovered from COVID-19 in Central Vietnam - Tran, Dinh Binh; Tran, Khanh Toan; Nguyen, Truong Son; Tran, Thanh Loan; Le, Hoang Gia Ngoc; Pham, Trung Hieu (Tạp chí Y Dược Huế, 2022)
Two years since the COVID-19 pandemic onset, the evidence base about post–COVID-19 conditions, also known as long COVID, is emerging. Studies showed that approximately 20%-70% patients may be suffered from the long COVID. Objectives: To preliminary assess the prevalence of post–COVID-19 condition and several related factors in COVID-19 patients in Thua Thien Hue province and Central Vietnam. Methods: A descriptive cross-sectional study was performed on people who have recovered from COVID-19 (confirmed by rapid antigen testing or PCR for SARS-CoV-2 result negative) for at least 2 weeks up to the time of the online survey using a questionnaire through the website: https://docs.google.com/forms/d/14ZvBAhhZjfW- gi3pIJ7j4f1OBSw2fQeym8M-XaXUtp8/edit. Results: 53 patients (21.2%) had persistent symptoms after at least 2 weeks of recovery. Of which, full-body weakness accounted for the highest rate (94.3%), followed by losing appetite or poor eating (90.6%). 86.3% of patients have a persistent cough, insomnia, and difficulty sleeping. Patients with headaches and dyspnea accounted for 69.5% and 56.8%, respectively, while other symptoms accounted for a lower rate. There was a statistically significant relationship between the time of infection, duration of disease, treatment place, use of sauna with herbal medicine, adherence to the *5K message from Vietnam’s Ministry of Health, saltwater mouthwash daily, and the prevalence of the post–COVID-19 condition (p<0.05). The use of antipyretic drugs, antibiotics, antiviral drugs, vitamins, and supplements was not related to the post–COVID-19 condition in our survey group (p>0.05). Conclusion: The post-COVID-19 condition is likely to become an important public health issue in the future, which may affect physical and mental health, and makes significant economic consequences for individuals, families, and society. A long-term survey is needed to accurately evaluate of the impact of post-COVID condition on patients.